Population Estimate of Anubis Baboon (Papio anubis) and Its Conflict With Farmers Around Kelebet Wonber Monastery, Antsokia Gemza District, North Shewa Zone, Amhara, Ethiopia - Destaw Gashaw; Dereje Yazezew (International Journal of Zoology, 2025)
Although Africa is endowed with a tremendous concentration of primate fauna, the conservation and management of these primates and their habitats is one of the foremost challenges. Excessive cases of human-primate conflict occur with baboons, which are notorious crop raiders and cause severe economic losses for farmers. A study on the population estimate of Anubis baboon (Papio anubis) and its conflict with humans was conducted from March 2022 to August 2022 during the dry and wet seasons around the Kelebet Wonber Monastery, Antsokia Gemza District, North Shewa Zone, Ethiopia. The direct total count method was used to estimate the abundance of Anubis baboon in the study area. Semistructured questionnaires were used to assess the perceptions and attitudes of local people toward Anubis baboons. All data were analyzed by using the SPSS version 26 computer software program. A total of 448 and 432 baboons were counted during the dry and wet seasons, respectively. There was no significant seasonal variation in Anubis baboon counts in the study area. Compared to the other blocks, Aballo Geregera had a significantly higher population of Anubis baboons. The population structure of Anubis baboon showed a higher proportion of females compared to males. Most (93.1%) of the respondents in the study area argued that Anubis baboons cause crop damage. Among the various techniques used to protect crops, permanent guarding (66.5%) was the most utilized method by farmers in the study area. The long-term survival of Anubis baboon is threatened unless stakeholders take mitigation measures to minimize the conflict between baboons and humans. Therefore, feasible mitigation measures should be launched to enhance the peaceful coexistence of both baboons and local communities in the area.